Alley Kat blues - Kijewski, Karen (New York : Bantam Books, 1995)
Kat Colorado finds the body of a young hit-and-run victim on the road and afterwords the mother of the victim comes to Kat's office to ask for her help--convinced that her daughter was murdered.
Adult.
Adult
Keywords: Colorado, Kat (Fictional character) -- Fiction; Colorado, Kat (Fictitious character) -- Fiction; Mormons -- Fiction; Mormons -- Fiction; Mystery fiction; Women detectives -- Fiction; Women detectives -- California -- Fiction; California -- Fiction; California -- Fiction; Mystery fiction